SUMBER DAYA MANUSIA PELATIH DALAM IMPLEMENTASI PROGRAM TPOK CABANG OLAHRAGA SEPAK BOLA DI KABUPATEN BATANGHARI - Feri Yose Rizal; Endarman Saputra; Reza Hadinata; Ugi Nugraha; Anggel Hardiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Coaching human resources are the most crucial component in the success of the Sub-district Sports Coaching Program (TPOK) for soccer in Batanghari Regency. This article aims to analyze the human resources aspects of coaches in the implementation of the TPOK Program, including qualifications and competencies, recruitment and selection processes, coaching experience, professional development efforts, and challenges faced. This study is based on qualitative research with a case study approach using the Van Meter and Van Horn policy implementation model. Data were collected through in-depth interviews with eight TPOK coaches (six with PSSI D licenses and two with AFC C licenses) and the Head of the Sports Division of the Batanghari Regency Youth and Sports Agency (Dispora Ekraf). The analysis results indicate that TPOK coaches have strengths in terms of formal qualifications, track records of experience, and high intrinsic motivation. However, there are significant weaknesses in the form of a disproportionate coach ratio (one coach per sub-district with dozens of villages), the absence of policy-facilitated advanced competency development programs, and limited budget support. This article recommends facilitating the upgrade of coach licenses from D to C AFC, establishing a sustainable competency development system, and reviewing the coach-to-area ratio as policy priorities.